‘An Important Exercise of Care and Attention’: How the International Geological Expedition Was Established in Mongolia - Narma A. Kamandzhaev (Oriental Studies)
Introduction. In the early 1970s, Mongolia’s executives ― in accordance with the Comprehensive Program of Socialist Economic Integration ― were seeking to gain economic ground and bring the MPR to the level of its partners. In this regard, a number of initiatives were put forward by CMEA, one be discussed herein. Goals. The article examines how CMEA bodies would coordinate the making of the International Geological Expedition in Mongolia. Materials. The source base for the study comprises both published and unpublished materials from the Russian State Archive of Economy and Russian State Archive of Contemporary History. Results. The approval of the Expedition’s establishment was a relatively long and non-linear process. The three-year review witnessed at least two appeals by the CMEA Standing Commission on Geology to the Executive Committee requesting due coordination of most controversial issues. Conclusions. The long and sometimes heated negotiation process resulted in that key provisions of the Agreement on the establishment of IGE were dramatically different from the initial proposals of the Mongolian side. The meetings of 1972–1973 proved decisive for the future functioning of the Expedition, since the former articulated the main goals of the endeavor. When it came to initiate such an expedition, the Mongolian side’s draft implied its work would be paralleled by arrangements on ‘issue no. 11’ to avoid any thematic overlaps, but this idea was opposed by the European socialist countries. In response, the July 1973 meeting launched a new initiative of the Mongolian side suggesting a detailed exploration of three deposits (a project of joint development was then being lobbied by Mongolian representatives in CMEA bodies). In our opinion, the contradictions were rooted in differing visions of the IGE’s goals adopted by Mongolia and European socialist countries. Nevertheless, the very fact of the IGE’s establishment in Mongolia can be viewed as a completely positive experience, since it was one of the few Mongolian initiatives within the CMEA that resulted in the signing of a multilateral agreement.